Nutrition of Genetically Improved Farmed Tilapia (GIFT) in biofloc technology system: Optimization of digestible protein and digestible energy levels during nursery phase - Sgnaulin T.* (2020)
© 2020 Elsevier B.V.The objective of the present work was to investigate different dietary digestible protein (22%, 26% and 30% of DP) and digestible energy (3000, 3150 and 3300 kcal DE kg−1) levels on growth performance and hematological parameters of Genetically Improved Farmed Tilapia (GIFT) fingerlings (0.99 ± 0.1 g of mean initial weight) over 42 days. In addition, proximate analysis of carcass and biofloc biomass, as well as planktonic community characterization were performed. A factorial design (digestible protein and digestible energy as factors) was applied totaling nine treatments with four replicates each. The FCR (~1.17) and survival (>98%) were similar between all treatments (P > .05). When assessing the final weight of the fish, in terms of weight gain and specific growth rate, the 22% and 26% DP treatments were not affected by the energy level (P > .05); however, the 30% DP level were affected by energy levels (P < .05) with best results using 3150 kcal DE kg−1. In regard to somatic parameters, carcass yield and condition factor of the fish were similar between all treatments (P > .05). Standard length presented an interaction effect (P < .05); while total length and the hepatosomatic index were affected by protein levels. Hematological parameters showed variability according to different dietary protein levels while carcass proximate composition was affected by both protein and energy levels (P < .05). The monitoring of planktonic communitities indicated some variation over the duration of the experiment, specifically on the number of dinoflagellates, rotifers and protozoa groups. These results suggest that the optimal digestible protein and digestible energy levels for tilapia fingerlings raised in freshwater biofloc systems are 26% DP and 3000 kcal DE kg−1.